(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
The Ban Ganga is an important tributary of river Chenab and flows thru the Katra metropolis of Jammu and Kashmir. Katra town is a prime commercial centre for Mata Vaishno Devi and additionally the main source of pollutants for Ban Ganga River & Tawi River. The river has non secular significance for Hindu Vaishnava and different devotees. more than 10 million site visitors make the pilgrimage each yr, and many bathes within the river to cleanse earlier than they go away on the whole journey. Holy Ban Ganga River, which is revered via the devotees and locals as sacred, has been definitely became a nallah where trash is flowing. The Ban Ganga River has been decreased to a -metre huge drain, full of sludge, plastic and litter of pilgrims a few pilgrims also raised worries over ecological degradation on the Trikuta mountain variety due to massive influx of Vaishno Devi pilgrims and alleged felling of trees, which immediately impacts the Ban Ganga River. Locals alleged that brisk developmental activities on the thirteen-km track from the Katra base camp to the cave shrine have been posing an ecological chance to the Trikuta hills and the largest assignment before the Board turned into to hold the ecological balance. They appealed Shrine Board as well as the Governor to take essential initiative to smooth Ban Ganga and feared that if emergency measures are not taken, the river would be dead soon. since the past few decades, Katra metropolis have skilled good-sized increase. the agricultural areas but, tormented by inadequate infrastructure facilities, were unable to address this swelling growth of the city regions a chief physical infrastructure issue that desires to be addressed within the Notified area is the inappropriate and unhygienic disposal of waste water & sewerage via open drains that follow the natural slope of land and its discharge, with none remedy. family who doesn’t have septic tank disposes their wastewater directly into drains which reveals its ultimate way into Ban-Ganga or herbal streams placed in the east and south east course of the town. The sewerage is being handled manually by using sweepers in a traditional manner and being thrown in open rain- water drains and herbal nallahs there via growing lot of pollution in town.PHE branch at Jammu is responsible for the distribution of water to the town and all the villages in the Notified region, extracts water from the Ban-Ganga Rivers, chlorinates it and then distributes it to all the city and villages. The great of this water is frequently inferior because of the infection of floor and surface water that consequences from the absence of a STP (Sewage treatment Plant) in the Notified place. the two water treatment plants have insufficient capacity to address the growing demand for water for the horizon 12 months. there is an absence of door-to-door waste collection practices inside the metropolis. most effective road sweeping is being practiced in the metropolis as a number one series of waste. there’s a scarcity of scientific waste disposal practices within the town. stable wastes generated from households and accommodations get disposed off alongside Katra - Reasi road without proper treatment. This has created nuisance in surrounding regions and makes difficult to skip from this avenue.